2004
DOI: 10.1136/jnnp.2003.025858
|View full text |Cite
|
Sign up to set email alerts
|

Dietary niacin and the risk of incident Alzheimer's disease and of cognitive decline

Abstract: Background: Dementia can be caused by severe niacin insufficiency, but it is unknown whether variation in intake of niacin in the usual diet is linked to neurodegenerative decline. We examined whether dietary intake of niacin was associated with incident Alzheimer's disease (AD) and cognitive decline in a large, prospective study. Methods: This study was conducted in 1993-2002 in a geographically defined Chicago community of 6158 residents aged 65 years and older. Nutrient intake was determined by food frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(89 citation statements)
references
References 42 publications
(28 reference statements)
5
79
0
2
Order By: Relevance
“…In the CHAP study, there was no association of vitamin supplement and/or food intake of folate, vitamin B12, or vitamin B6 to 4-year risk of Alzheimer's disease [29]. However, the CHAP study did find greater AD risk and faster rate of cognitive decline among persons whose consumption of niacin was low [32].…”
Section: Evaluating the Epidemiologic Evidencementioning
confidence: 87%
“…In the CHAP study, there was no association of vitamin supplement and/or food intake of folate, vitamin B12, or vitamin B6 to 4-year risk of Alzheimer's disease [29]. However, the CHAP study did find greater AD risk and faster rate of cognitive decline among persons whose consumption of niacin was low [32].…”
Section: Evaluating the Epidemiologic Evidencementioning
confidence: 87%
“…In contrast, the studies that examined the association of vitamin B 12 with AD were null (159,(176)(177)(178)(180)(181)(182) . There have been a number of randomised trials of the effects of supplementation with folic acid and vitamin B 12 on cognitive decline.…”
Section: B-vitamins Cognitive Decline and Alzheimer's Diseasementioning
confidence: 91%
“…A number of prospective studies that examined the relation between folate and dementia found inverse associations (176)(177)(178)(179)(180) , although several studies did not (159,181,182) . In contrast, the studies that examined the association of vitamin B 12 with AD were null (159,(176)(177)(178)(180)(181)(182) .…”
Section: B-vitamins Cognitive Decline and Alzheimer's Diseasementioning
confidence: 99%
“…The selection of dietary covariates is based on previous CHAP studies. [19][20][21] The interaction terms with time represent the effects of the variables on the rate of change in cognitive score. Because a large portion of the sample was not included in the analyses, models were not weighted for the stratified random sampling design.…”
Section: Methods Study Populationmentioning
confidence: 99%